Mechanical Properties of Glassy Nanopillars: A Comparative, Computational Study of Size Effects in Nanoglasses and Homogeneous Bulk Glasses - Adjaoud, Omar; Albe, Karsten (Frontiers in Materials, 2020)
We study the mechanical properties of nanoglass (NG) nanopillars with diameters from \unit[4.5]{nm} to \unit[54]{nm} by means of molecular dynamics simulations and compare the results with those obtained for nanopillars prepared from homogenous bulk glasses. Nanoglass nanopillars of two different types of glasses, namely Cu$_{64}$Zr$_{36}$ and Pd$_{80}$Si$_{20}$, were cut from samples prepared by nanoparticle consolidation. The influence of nanopillar diameter on the deformation behavior and strain localization is investigated. Moreover, cyclic loading is used to explore the origin of stress overshoots in the stress-strain curves of NGs. Finally, from the calculated properties a deformation map for NG and HG nanopillars is derived.